Cactodera chenopodiae (Nematoda: Heteroderidae), a new species of cyst nematode parasitizing common lambsquarter (Chenopodium album) in Liaoning, China - Feng, Yaxing; Wang, Dong; Xiao, Dongxue; Pereira, Tiago José; Xuan, Yuanhu; Wang, Yuanyuan; Liu, Xiaoyu; Chen, Lijie; Duan, Yuxi; Zhu, Xiaofeng (Zootaxa, 2018)
A new species of cyst nematode, Cactodera chenopodiae n. sp., parasitizing common lambsquarter, Chenopodium album L., is described from native vegetation in Liaoning, China. Cactodera chenopodiae n. sp. has a circumfenestrate pattern typical of the genus and is morphologically similar to C. cacti Krall & Krall, 1978. However, in the new species, females and cysts show a larger L/W ratio whereas second-stage juveniles (J2s) have a longer hyaline region. The new species is also morphologically similar to C. milleri Graney & Bird, 1990, but the J2s differ by a larger b ratio and longer tail. Based on DNA sequences of the 28S and ITS rRNA, C. chenopodiae n. sp. comes close to C. estonica Krall & Krall, 1978, although it is distinct from the latter with respect to the presence of a punctate eggshell and larger b ratio in the J2s. Although morphometric comparisons with additional Cactodera species show the overlapping of diagnostic morphological characters, our phylogenetic analyses based on both rRNA genes support C. chenopodiae n. sp. as a unique lineage.